The Effect of MMP-2 Inhibitor 1 on Osteogenesis and Angiogenesis During Bone Regeneration - Jiang, Liangjun; Sheng, Kunkun; Wang, Cong; Xue, Deting; Pan, Zhijun (Frontiers in Cell and Developmental Biology, 2021)
Bone regeneration is a popular research focus around the world. Recent studies have suggested that the formation of a vascular network as well as intrinsic osteogenic ability is important for bone regeneration. Here, we show for the first time that matrix metalloproteinase (MMP) 2 inhibitor 1 (MMP2-I1) has a positive role in the osteogenesis of human bone marrow mesenchymal stem cells (hBMSCs) and angiogenesis of human vascular endothelial cells (HUVECs). MMP2-I1 activated the p38/mitogen-activated protein kinase signalling pathway to promote the osteogenesis of hBMSCs, and promoted the angiogenesis of HUVECs via the hypoxia-inducible factor-1α signalling pathway. We also found that MMP2-I1 enhanced bone formation using a rat tibial defect model and prevented bone loss using an ovariectomy-induced mouse model of osteoporosis. Data from the mouse model demonstrated that MMP2-I1 generated more type H vessels (CD31hiEmcnhi) when preventing bone loss. These results provide important insights into the regulatory effects of MMP2-I1 on bone regeneration.